Protective effect of salvianolic acid B against myocardial ischemia/reperfusion injury: preclinical systematic evaluation and meta-analysis - Yang, Yuhan; Sun, Ziyi; Sun, Xiaoning; Zhang, Jin; Tong, Tong; Zhang, Xiaoxiao; Yao, Kuiwu (Frontiers in Pharmacology, 2024)
Background: Salvianolic acid B is the most abundant water-soluble component in the traditional Chinese medicine Danshen and can reduce myocardial ischemia-reperfusion (MI/R) injury through multiple targets and pathways. However, the role of SalB in protecting the myocardium from ischemia/reperfusion injury remains unclear. Purpose: To perform a preclinical systematic review and meta-analysis to assess the efficacy of Sal B in an animal model of myocardial infarction/reperfusion (MI/R) and to summarize the potential mechanisms of Sal B against MI/R. Methods: Studies published from inception to March 2024 were systematically searched in PubMed, Web of Science, Embase, China National Knowledge Infrastructure (CNKI), Wanfang, and VIP databases. The methodological quality was determined using the SYRCLE RoB tool. The R software was used to analyze the data. The potential mechanisms are categorized and summarized. Results: 32 studies containing 732 animals were included. The results of the meta-analysis showed that Sal B reduced myocardial infarct size (p < 0.01), and the cardiological indices of CK-MB (p < 0.01), CK (p < 0.01), LDH(p < 0.01), and cTnI (p < 0.01) compared to the control group. In addition, Sal B increased cardiac function indices, such as LVFS (p < 0.01), -dp/dt max (p < 0.01), +dp/dt max (p < 0.01), and cardiac output (p < 0.01). The protective effects of Sal B on the myocardium after I/R may be mediated by attenuating oxidative stress and inflammation, promoting neovascularization, regulating vascular function, and attenuating cardiac myocyte apoptosis. Publication bias was observed in all the included studies. Further studies are required to elucidate the extent of the cardioprotective effects of SalB and the safety of its use. Conclusions: To the best of our knowledge, this is the first meta-analysis of Sal B in the treatment of MI/R injury, and Sal B demonstrated a positive effect on MI/R injury through the modulation of key pathological indicators and multiple signaling pathways. Further studies are needed to elucidate the extent to which SalB exerts its cardioprotective effects and the safety of its use.